Media reach and reception in development communication: the case of the Rural Industries Innovation Centre in Botswana - Maleke, Jackson Mogopodi (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 1998)
The study was conducted in Phitshane-Molopo in Botswana. Phitshane-Molopo is located about 115 kilometers south of the main village of Kanye in which the Rural Industries Innovation Centre operates. The study constitutes the first attempt at evaluating audience reach and reception of the RIIC media messages. In this study, a sample of 50 representatives of households (the rationale is covered in chapter 1) was taken, for which a questionnaire was administered, including conducting in-depth interviews with key informants. The study found that RIlC media are not reaching the audience in keeping with the corporate goals and assumptions on the basis of which the communication strategy was established. The audience has claimed that the print media relayed to them through the extension officer channel do not reach them. The study also found that the audience possessed adequate literacy skills and the majority of them could read materials produced in Setswana. Only a few individuals preferred media text produced in the English language. The study therefore deplores RIIC's proclivity towards producing its media texts only in the English language. This has tended to marginalise members of the audience who cannot read in English. It is thus hoped that this study would provide a learning experience for RIIC to consider producing its communication media in relation to the needs of the audience. The study also found that the impact of the RIIC radio programme is very poor, with only a low of 2% of the sample population having listened to this programme. The problem stems from the poor Radio Botswana transmission system. The audience said that for the larger part of the day, they can't get Radio Botswana on air. As a result, they have shifted their interest to the South African radio stations such as Radio Tswana and Radio Mmabatho, which are constantly on air. The study concludes that the RIIC communication strategy is failing in the study area because the paradigm in which it is located is somewhat flawed, as a result of which it does not effectively impact upon reach and reception. At the core of this failure rate are implementation problems and the lack of evaluation that would have picked up the - problems earlier, for which solutions would have been found. Consequently, th~$tudy recommends the need to explore the suitability and effectiveness of the indigenous media for possible syncretization with conventional media as recommended in the need based integrative model (Nwosu and Megwa: 1993). Indigenous media are ideally suited to rural communication needs because they are consistent with the socio-cultural expectations of the audience. RIIC therefore stands to benefit from these media because the bulk of its audience resides in rural areas.
Keywords: Rural Industries Innovation Centre (Kanye, Botswana); Communication in rural development; Mass media in community development